Synthesis of Ti1-xWx solid solution MAX phases and derived MXenes for sodium-ion battery anodes - Ratzker, Barak; Favelukis, Bar; Baranov, Mark; Rathod, Yugal; Greenberg, Avia; Messer, Or; Goldstein, Dor A.; Upcher, Alexander; Ezersky, Vladimir; Maman, Nitzan; Biran, Ido; Natu, Varun; et al. (ADVANCED FUNCTIONAL MATERIALS, 2024)
Keywords: Behavior; CARBIDE MXENE; INTERCALATION MECHANISM; TI

TiO2 spaghetti for sustainable future - Rathod, Yugal; Natu, Varun (Matter, 2024)
TiO2 is widely utilized in applications ranging from paints to solar cells. Recent advancements in synthesizing nano-TiO2 by Badr, Barsoum, et al. have enabled its production at low cost and large scale. These nanostructures, comprising 1D lepidocrocite nanofilaments, show promise in enhancing solar water splitting and several other applications.